The second rural energy project = (The World Bank in Vietnam (WB), 2004)
The objective of the Additional financing for Second Rural Energy Project is to improve access to good quality, affordable electricity services to rural communities in an efficient and sustainable manner, to support Vietnam's efforts towards socioeconomic development. The global environment objective is to reduce greenhouse gas emissions by improving and sustaining the energy efficiency of local distribution utilities. The additional credit will help finance the costs associated with: (a) completion of the original project activities as a result of an unanticipated financing gap. It will enable completion o f the original target of about 1,200 communes, compared with the current expectation of about 968; and (b) implementation of expanded activities that will scale up the project's impact and development effectiveness by increasing the number of communes from 1,200 to 1,500. As a result of the two uses of the additional financing, an estimated 532 communes or about 5 50,000 households will receive access to good quality, affordable electricity.